Surface plasmon resonance (SPR) based temperature and magnetic field sensor in a dual-core D-shaped photonic crystal fiber (PCF). Issue 3 (17th October 2021) - Wang, Jia-Kai; Ying, Yu; Gao, Zhi-Jun; Cheng, Si-Yu; Si, Guang-Yuan
Abstract: A high sensitivity surface plasmon resonance (SPR) based temperature and magnetic field sensor in a dual-core D-shaped photonic crystal fiber (PCF) with two types of holes is reported. The flat surface of the dual-core D-shaped PCF is coated with ethanol as the temperature-sensitive material. A large diameter hole coated with a gold ring is filled with a magnetic fluid as a magnetic field-sensitive material. Using the finite element method (FEM), the electric field distribution mode is simulated, and the loss spectra of the temperature sensing channel (channel I) and magnetic field sensing channel (channel II) are calculated. The influence of the types of metal films and rings, large hole diameter, small hole diameter, and gold film and gold ring thicknesses on the sensor performance are discussed. The results showed that the reported sensor is able to measure temperature and magnetic field independently and simultaneously due to its dual channels. The influence of temperature on magnetic field measurements is reduced by reducing the hole diameter. The results show that the temperature sensitivity is 1.151 nm/°C and the correlation coefficient is 0.9954 from 20 to 70 °C. The magnetic field intensity sensitivity is 0.0779 nm/Oe from 25 to 200 Oe and 0.0212 nm/Oe from 200 to 275 Oe with correlation coefficients of 0.9937 and 0.9989 across these ranges. This high sensitivity D-shaped PCF sensor will promote the development of high-performance dual-parameter devices.